Analisis biaya pelayanan gizi keluarga miskin di Kabupaten Indragiri Hulu - Elis Julinarti; Hamam Hadi; Tubagus Raymond (Jurnal Gizi Klinik Indonesia, 2005)
Background: The health cost from both government and non-government sectors in the year of 2000 was Rp1.470/ capita/year. The cost for nutrition programs in the year 2003 was Rp200/ capita/ year, while in Indragiri Hulu, the cost for nutrition service was allocated 0.55% of regional budget of Health Department.Objective: To estimate the real cost and demand of cost of nutrition service for poor family and to explore the perception of regional government, regional parliament and private sectors about the cost of nutrition service.Method: This study was a qualitative study. In-depth interview method was used to collect data from regional government officers, regional parliament members and private sectors.Results: The cost of nutrition service for poor family on average was Rp12.053.000, in the year 2003 and Rp8.763.000, in the year 2004. In fact, the demand cost was Rp79.022.541, for rural primary health care and Rp144.073.000, for urban primary health care.Conclusion: The cost of nutrition service for poor family in Indragiri Hulu on average was Rp645/ capita/ year in the year 2003 and Rp355, in the year 2004 which was much smaller than the demand cost which was Rp14.290.